Dynamics of Monetary-Fiscal Interaction under Learning - Josef Hollmayr; Christian Matthes (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The interaction between monetary and fiscal policy and the associated uncertainty about this interaction have been put on center stage by the recent financial crisis and the associated recession. In our model agents learn about both fiscal and monetary policy rules via the Kalman Filter. In particular, we study how an economy populated with agents acting as econometricians reacts to discrete changes in the actual policy rules.
Keywords: E32; D83; E62; 330